Juglone and 1,4-Naphthoquinone—Promising Nematicides for Sustainable Control of the Root Knot Nematode Meloidogyne luci - Maleita, Carla; Esteves, Ivânia; Braga, Mara E. M.; Figueiredo, Joana; Gaspar, Marisa C.; Abrantes, Isabel; Sousa, Hermínio C. de (Frontiers in Plant Science, 2022)
The scarce availability of efficient and eco-friendly nematicides to control root-knot nematodes (RKN), Meloidogyne spp., has encouraged research toward the development of bionematicides. Naphthoquinones, juglone (JUG) and 1,4-naphthoquinone (1,4-NTQ), are being explored as alternatives to synthetic nematicides to control RKN. This study expands the knowledge on the effects of these natural compounds toward M. luci life cycle (mortality, hatching, penetration, reproduction). M. luci second-stage juveniles (J2)/eggs were exposed to each compound (250, 150, 100, 50, and 20 ppm) to monitor nematode mortality and hatching during 72 h and 15 days, respectively. Tomato seedlings were then inoculated with 200 J2, which had been exposed to JUG/1,4-NTQ for 3 days. The number of nematodes inside the roots was determined at 3 days after inoculation, and the final population density was assessed at 45 days after inoculation. Moreover, the potential mode of action of JUG/1,4-NTQ was investigated for the first time on RKN, through the assessment of reactive oxygen species (ROS) generation, acetylcholinesterase (AChE) in vitro inhibitory activity and expression analysis of ache and glutathione-S-transferase (gst) genes. 1,4-NTQ was the most active compound, causing ≥50% J2 mortality at 250 ppm, within 24 h. At 20 and 50 ppm, hatching was reduced by ≈50% for both compounds. JUG showed a greater effect on M. luci penetration and reproduction, decreasing infection by ≈80% (50 ppm) on tomato plants. However, 1,4-NTQ-induced generation of ROS and nematode vacuolization was observed. Our study confirms that JUG/1,4-NTQ are promising nematicidal compounds, and new knowledge on their physiological impacts on Meloidogyne was provided to open new avenues for the development of innovative sustainable nematicides.